Analysis of factors and drivers in graduates success among Portugal, India and Italy –defining success - Pereira, Maria Leonor Água Alves Pacheco (2021)
Success emerges as a very wide concept. This project aims to understand the factors and drivers in graduates’ success across Portugal, India and Italy. The present research is focused on the factors that account for these graduates’ definition of success. The study analyzed the topic following an exhaustive exploratory research, which started with the collection of secondary data to support and better understand the topic, followed by a valuable qualitative research which used in-depth interviews to obtain rich insights. These first two steps retrieved the guidelines to create a questionnaire for the quantitative component. After analyzing the results and establish the most adequate relationships, it was found that this generation of business graduates identify success as being composed by career and personal achievement, albeit they highly associate overall success as a well balanced and meaningful life, in detriment to material goods. These results are of great value to the higher education institutions, who have the power to interfere in these factors and better tailor their services offer to students’ expectations and aspirations.